Violência no município de Natal/RN em 2019 e 2020: uma abordagem espacial e demográfica sobre as mortes violentas com foco nos efeitos decorrentes da pandemia da COVID-19 - Freitas, Pedro Henrique Oliveira de (2021)
Violence is a material mechanism that has always been present in human society, manifesting itself in a painful, dangerous and unequal way. With regard to Brazil, since the 1980s, homicides are the second leading cause of death in population groups aged 15 to 39 years, especially in males. In order to explain this phenomenon that is so present in the daily life of large urban centers, several fields of knowledge began to point out factors such as poverty, income inequality and the absence of the State, which are crucial for the maintenance of high levels of violence in the country. However, few works discuss the theme based on the use of spatially disaggregated information, at the level of geographic coordinates, for analysis in urban space. Given this context, the work aims to analyze the distribution of CVLIs (Intentional Violent Violent Crimes) in the intraurban space of Natal/RN, in the years 2019 and 2020, to analyze the characteristics and locational pattern of these deaths, taking into account the heterogeneity of the urban space in relation to the sociodemographic characteristics of the population, and the dependence on socio-spatial segregation. The choice for the years 2019 and 2020 was made with the objective of analyzing the spatial distribution of CVLIs in a prepandemic period and during the pandemic, in order to verify the effects of the pandemic on the phenomenon of violence in Natal/RN, its permanence or alterations, either in relation to the spatial distribution of homicides, or in relation to the intensity and profile of the occurrences. The data sources used were the Rio Grande do Norte Violence Observatory, the Municipal Department of Environment and Urbanism and the 2010 Demographic Census. Kernel interpolation, autocorrelation, added to the use of satellite images. The results showed the concentration of violent spaces in the North and West portions of the city, with high percentages of CVLIs in these areas due to drug trafficking, mortality among the young population and the strong relationship between this phenomenon and areas that present greater socio-spatial vulnerability. Furthermore, it was possible to observe some differences in relation to the spatial distribution of CVLIs, and especially in relation to the characteristics of violence observed between 2019 and 2020.